Ricardo Palma in the republican dawn - Arista Montoya, Luis Alberto (2020)
The present article explains Ricardo Palma’s historical perspective through his traditions related to the ups and downs of the fight for the new power generated by civil and military factions of the criolla political class in the Emancipation context. Some of Palma’s political traditions about the difficult transition from the colonial era to the democratic republican era are key documents for understanding the new historical time. There were many more shadows than lights in that Emancipation.